Heat treatment to regulate bismuth valence toward enhanced radiation resistance in barium gallo‐germanate glass. Issue 2 (26th October 2022) - Yan, Na; Xiong, Puxian; Liu, Bingjun; Tian, Shuhang; Song, Xiangyang; Shi, Zhenguo; Xiao, Yao; Sun, Yongsheng; Wu, Minbo; Wei, Ben; Tang, Guowu; Qian, Qi; et al.
Abstract: Due to the excellent infrared transparency, low phonon energy, and high rare‐earth solubility, germanate laser glass has attracted much attention in mid‐infrared fiber lasers for potential coherent laser radar systems, optical detection, remote sensing, and laser surgery. However, radiation‐induce darkening often occurs in fiber lasers that operate in radiation environment. Here, we report a useful strategy to improve the radiation resistance by adding multivalence Bi ions and discuss its radiation resistance mechanism. In order to study the effect of valence states on the radiation resistance of barium gallo‐germanate glass, we adjust the valence states of Bi ions by heat treatment, the potential mechanism of which is discussed in detail based on the absorption, photoluminescence (PL), and Raman spectra. The absorption, electron paramagnetic resonance, and photoluminescence spectra have proved the interconversion of Bi ions between low and high valence, which inhibits the formation of Ge‐related electron center (GEC) and non‐bridging oxygen hole center defects in the irradiation process. In addition, the Bi 3+ content increased by heat treatment is beneficial to serve as electron‐trapping centers in γ‐ray irradiation, thus further reducing the formation of GEC. This study provides a simple method to achieve Bi valence regulation, so as to improve the radiation resistance.